2014
DOI: 10.1111/jpn.12218
|View full text |Cite
|
Sign up to set email alerts
|

Differences in monocarboxylic acid transporter type 1 expression in rumen epithelium of newborn calves due to age and milk or milk replacer feeding

Abstract: The aim of the present study was to investigate whether besides age and solid feed intake, monocarboxylic acid transporter type 1 (MCT1) expression in the rumen epithelium of calves is affected by liquid feed type [whole milk (WM) or milk replacer (MR)]. Thirty bull calves at the mean age of 5 days were randomly allocated to five experimental groups (six calves/group). Six calves were slaughtered immediately after allocation to the trial (5 days of life), eighteen calves were fed MR and slaughtered at week int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
3
7
1
Order By: Relevance
“…This result is similar to a previous study for the MCT1 short-chain fatty acid transporter, whose abundance did not differ between dorsal and ventral sacs in developing calves (Flaga et al 2015). Since we have previously reported that UT-B2 transporters are constitutively activated (Tickle et al 2009), this strongly suggests that overall there will be no difference in UT-B mediated trans-epithelial transport in different ruminal sacs at the cellular level.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to a previous study for the MCT1 short-chain fatty acid transporter, whose abundance did not differ between dorsal and ventral sacs in developing calves (Flaga et al 2015). Since we have previously reported that UT-B2 transporters are constitutively activated (Tickle et al 2009), this strongly suggests that overall there will be no difference in UT-B mediated trans-epithelial transport in different ruminal sacs at the cellular level.…”
Section: Discussionsupporting
confidence: 91%
“…These factors also trigger activation of downstream targets that can mediate rumen development and function in growing calves12. Changes of monocarboxylate transporter 1 ( MCT1 ) expression occur in an age-dependent manner in the rumen epithelium of neonatal calves, which suggests that the expression of MCT1 may be affected by the provision of liquid feed13. During the studies described above, many changes in gene expression related to rumen development were identified in calves.…”
mentioning
confidence: 99%
“…A recent study reported that gene expression related to rumen development shows dynamic change between preweaning and postweaning calves (Kato et al, 2016). Flaga et al (2015) showed that age-dependent increase in MCT1 gene expression was detected in the rumen of calves before weaning (Flaga et al, 2015). Age-dependent changes of MCT4 and CD147, however, have not been investigated in calves even if those are significant for absorption of SCFAs.…”
Section: Introductionmentioning
confidence: 99%